Newer glucose‐lowering drugs reduce the risk of late‐onset seizure and epilepsy: A meta‐analysis - Udeept Sindhu; Akshay Sharma; Ifrah Zawar; Vineet Punia (Epilepsia Open)
Abstract Newer glucose‐lowering drugs (GLDs) protect against cerebrovascular, neurodegenerative, and neuroinflammatory pathologies. Therefore, we performed a meta‐analysis of randomized controlled trials (RCTs) comparing newer GLDs to placebo that assessed long‐term cardiovascular and renal outcomes to analyze their potential to prevent late‐onset seizures and epilepsy, separately and as a combined outcome. A comprehensive MEDLINE and CENTRAL databases search for DPP‐4 inhibitors, GLP‐1 receptor agonists, and SGLT2 inhibitor RCTs, which reported adverse effects, including seizures and epilepsy on clinicaltrials.gov, yielded 413 studies. Of them, 27 studies with almost 200 000 patients (mean age 64.9 years, 65.6% males) were included. We calculated relative risk (RR) and odds ratio (OR) using the Mantel–Haenszel method and Peto's method. Patients taking newer GLDs had a 24% lower risk of late‐onset seizures and epilepsy, combined, (RR: 0.76, 95% CI: 0.62–0.95) and 22% lower risk of late‐onset seizures only (RR = 0.78; 95% CI = 0.60–1.00), compared to patients on placebo. This seizure and epilepsy prevention benefit was only noted among patients taking GLP‐1 receptor agonists. Stroke incidence was comparable between newer GLDs and placebo group. GLP‐1 receptor agonists like Semaglutide significantly reduce late‐onset seizures and epilepsy, and their anti‐epileptogenic potential in older adults needs further exploration. Plain Language Summary Our analysis 27 clinical trials and nearly 200 000 patients evaluated the potential of newer glucose‐lowering drugs (GLDs) to prevent late‐onset seizures and epilepsy in older adults. The study found that newer GLDs, especially GLP‐1 receptor agonists like Semaglutide, reduced the combined risk of seizures and epilepsy by 24% compared to placebo. These findings suggest that newer GLDs may offer prevention against the development of seizures and epilepsy in older adults. However, further research is needed to confirm their anti‐epileptogenic effects.